Biosynthesis of silver nanoparticles-eggshell nanocomposite using Garcinia Mangostana L. Leaf extract and its application for the reduction of 4-nitrophenol - Mohd. Tubillah, Norfarahim (2020)
In recent years, metal nanoparticles have attracted wide attention due to their attractive properties and interesting applications. In particular, the catalytic properties of silver nanoparticles (Ag NPs) are of interest to many researchers because of their high reactivity. This study reported the synthesis of Ag NPs using Garcinia mangostana L. leaf extract as reducing and stabilizing agent. The biosynthesized Ag NPs were then immobilized on the surface of eggshell powder. The formation of Ag NPs were confirmed by the presence of absorption peak at 450 nm and the bioreduction reaction was completed within 4 h as monitored by ultraviolet-violet (UV-Vis) spectroscopy. The Fourier transform infrared spectroscopy (FTIR) analysis on the Garcinia mangostana L. leaf extract revealed the presence of -OH functional groups that were involved in the reduction and stabilizing of Ag NPs. Energy dispersive X-ray (EDX) analysis on the AgNPs/eggshell nanocomposite showed the presence of Ag peaks that indicated the successful immobilization of Ag on the eggshell powder. The X-ray diffraction (XRD) analytical data on the nanocomposite showed a series of diffraction peaks that are consistent with crystalline CaCO3 from the eggshell and metallic Ag. From TEM images, Ag NPs were mostly of spherical shape with a mean diameter of 14.6 nm. The synthesised AgNPs/eggshell nanocomposite was tested as catalyst for the reduction of 4-nitrophenol to 4-aminophenol in the presence of sodium borohydride at room temperature. The highest activity was observed for the AgNPs/eggshell nanocomposite with Ag loading of 6 wt% and 4-nitrophenol with concentration of 0.03 mM. Under these optimum conditions, the 4-nitrophenol reduction showed good reproducibility where the average rate of reaction is 0.1478 min-1 while the average percentage of reduction calculated is 98.49%. From the recyclability test, the AgNPs/eggshell nanocomposite gave a slight decreased in catalytic activity within three catalytic cycles due to mass loss.